2002
DOI: 10.1076/ceyr.25.5.299.13495
|View full text |Cite
|
Sign up to set email alerts
|

Human Schlemm's canal cells express the endothelial adherens proteins, VE-cadherin and PECAM-1

Abstract: Purpose. The majority of resistance to outflow of aqueous humor resides at or near the inner wall of Schlemm's canal (SC). Transmembrane proteins that contribute to the generation of resistance to aqueous outflow likely participate in junctional complexes between SC cells. The purpose of the present study was to examine the expression of cadherins in SC cells that play a significant role in adherens junction complexes that control permeability of vascular endothelia. Methods. Identification of cadherin subtype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 41 publications
(45 reference statements)
3
45
0
Order By: Relevance
“…(Heimark et al 2002;Chen et al 2005;Vittal et al 2005) A variety of other cell-surface receptors and cellcell interaction proteins are expressed by TM/SC cells. These include sarcoglycan β and ε, dystroglycan and sarcospan, which are members of the dystroglycan glycoprotein complex that can serve as a laminin receptor in some tissues.…”
Section: Cell-surface Ecm Receptors Of the Tmmentioning
confidence: 99%
“…(Heimark et al 2002;Chen et al 2005;Vittal et al 2005) A variety of other cell-surface receptors and cellcell interaction proteins are expressed by TM/SC cells. These include sarcoglycan β and ε, dystroglycan and sarcospan, which are members of the dystroglycan glycoprotein complex that can serve as a laminin receptor in some tissues.…”
Section: Cell-surface Ecm Receptors Of the Tmmentioning
confidence: 99%
“…It has been postulated by several investigators (Epstein and Rohen, 1991;Alvarado et al, 1998;Brandt and O'Donnell, 1999;Underwood et al, 1999;Rao et al, 2001;Heimark et al, 2002) that instead of passing through the pores in the inner wall endothelium, a significant fraction of the aqueous humour passes through gaps between the tight junction strands of these cells. Ethier and Chan (Ethier and Chan, 2001) found that cationized ferritin perfused into enucleated human eyes acted to decreased outflow facility and was seen accumulating near junctions between inner wall endothelial cells.…”
Section: Pores As Possible Fixation Artifacts and The Possible Importmentioning
confidence: 99%
“…22 Of note is that, among the cadherin family junctional genes being expressed, VEcadherin was not tested in these arrays, nor was PECAM, both reported to be expressed in SC cells in culture. 23,24 Fibulin 2, also reported in SC cells, 24,25 was also not tested in this array, but fibulin 1 was much higher in SC cells. The fibulins are interesting as an elastic component of the ECM and basement membrane.…”
Section: Resultsmentioning
confidence: 85%
“…Thus, our results are consistent with an endothelial identity of the SC cells. 5,23,24,28 One interesting question is what role chitinase family proteins play in the outflow pathway. Liton et al showed that the chitinase 3-like 1 gene was strongly overexpressed in TM cells relative to SC.…”
Section: Resultsmentioning
confidence: 99%